Adopting orphan receptors: zebrafish Tlr4 homologs mediate responses to group IX/X transition metals - Fox, Aaron P.D.; Lee, Tracy S.; Mithaiwala, Sakina N.; Pollock, Niall M.; Latif, Asna; Bhavsar, Amit P.; Allison, W. Ted (Frontiers in Immunology, 2025)
TLR4 is the prototype immune receptor and central to infection defense via detecting lipopolysaccharide (LPS). Surprisingly, the impacts of LPS upon the TLR4 homologs in zebrafish, an important animal model, are equivocal and the function of TLR4 homologs across all fishes remains debatable. Recent work suggests zebrafish Tlr4 mediates ototoxic responses to a platinum-based chemotherapeutic. This prompts our hypothesis that Tlr4 detects group IX/X transition metals and thus has conserved roles with human TLR4 mediating allergic responses to nickel. Here, we use the larval zebrafish lateral line model to demonstrate (sub-)micromolar Ni, Co and Pt are ototoxic in a dose-dependent manner. TLR4 homologs are required for this toxicity because Tlr4 knockdown via CRISPR significantly reduced the metals’ impacts by ~50%. Moreover, zebrafish Tlr4 was sufficient to mediate inflammatory responses to metals when expressed in a human cell line. These data show zebrafish TLR4 homologs are necessary and sufficient to mediate responses to metals, however, direct biophysical binding of metals to zebrafish TLR4 homologs remains uninvestigated. These data are consistent with the notion that mediating responses to transition metals was a function of TLR4 homologs in the last common ancestor of fish and mammals, and begins to resolve the function(s) of TLR4 homologs in the zebrafish animal model of disease.